Effect of Health Education on Health Behavior in Patients with Hypertension - Nur Haryani; AA. Subiyanto; Nunuk Suryani (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Hypertension is a disease that can lead to stroke, heart attack, heart failure that can lead to death. Someone who has a risk factor for hypertension must be more vigilant and earlier in conducting prevention efforts. Prevention is to control the blood and improve the understanding of hypertension through health education in order to identify and reduce risk behavior hypertension. The purpose of this study was to determine the effect health education program 0n health behavior in patients with hypertension.Subjects and Method: This was a quasi-experimental study with pretest-posttest and control design. This conducted in Purwo Bakti Husodo, Purwodiningratan and Mojosongo integrated development post Pos Pembinaan Terpadu (Posbindu). A total sample of patients with hypertension as many as 30 people the treatment group and 32 control group. Data analysis using paired sample t-test or Wilcoxon and using independent sample t-test or Mann Whitney.Results: No effect of hypertension health education to the knowledge of hypertension (p<0.001). There is an effect on the attitudes of health education hypertension patients with hypertension (p=0.014). Health education hypertension influence the change risky behavior is a history of smoking (p=0.005), eating salty foods (p=0.008) and frequency of exercise (p 0.001), while health education hypertension had no effect statistically significant to change risky behavior that is stress (p=0.322) and BMI (p=0.502).Conclusion: Health education about hypertension effect on knowledge, attitudes, smoking, eating salty foods and exercise while no effect on stress and Body Mass Index (BMI).Keywords: health education, knowledge, attitudes and behavior of hypertension risk.Correspondence: Nur Haryani. School of Public Health, Sebelas Maret University, Surakarta.Journal of Health Promotion and Behavior (2016), 1 (1): 9-18https://doi.org/10.26911/thejhpb.2016.01.01.02